2015
DOI: 10.7439/ijbar.v6i1.1492
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clonidine and tramadol for the control of shivering under spinal anaesthesia

Abstract: Objectives: This study aimed to evaluate the relative efficacy of intravenously administered clonidine and tramadol for control of intraoperative shivering following spinal anaesthesia. Materials and Methods: A prospective, randomized, clinical controlled study was conducted on 60 ASA grade-I &II patients of either sex, aged 18-40 years, scheduled for elective lower abdominal and lower limb surgeries, under spinal anaesthesia. Patients who developed post spinal intraoperative shivering of grades 3 or 4, lastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…For instance, there was a randomized clinical trial conducted by Prerna Attal et al, on patients undergoing abdominal and lower extremities surgery, to compare the effect of Clonidine and Tramadol on spinal anesthesia-related shivering. Their findings indicated that the time required for stopping shivering and improving the patients' condition was significantly lower in the Tramadol group (3.16±0.84 min) than the Pethidine group (5.76±0.8 min); yet, there was no significant statistical difference between the Tramadol and Clonidine groups in terms of heart rate, systolic blood pressure, and diastolic blood pressure (Attal et al, 2015).…”
Section: Discussionmentioning
confidence: 84%
“…For instance, there was a randomized clinical trial conducted by Prerna Attal et al, on patients undergoing abdominal and lower extremities surgery, to compare the effect of Clonidine and Tramadol on spinal anesthesia-related shivering. Their findings indicated that the time required for stopping shivering and improving the patients' condition was significantly lower in the Tramadol group (3.16±0.84 min) than the Pethidine group (5.76±0.8 min); yet, there was no significant statistical difference between the Tramadol and Clonidine groups in terms of heart rate, systolic blood pressure, and diastolic blood pressure (Attal et al, 2015).…”
Section: Discussionmentioning
confidence: 84%
“…Possível agonista α2 adrenérgico no sistema nervoso central (SNC) e antagonista não competitivo dos receptores NMDA espinhais (GANI, et al, 2016;FERN & MISIRIN, 2015), b) Tramadol (35 a 220mg): inibição da recaptação de 5HT, noradrenalina e dopamina, aumento da liberação de 5HT reduzindo o set point da temperatura corporal. Possível agonista α2.1 (HINDSHOLM, et al, 1992;JAVAHERFOROOSH, et al, 2009;ATTAL, et al, 2015;RASHWAN, et al, 2015;TREKOVA, et al, 2004). c) Outros: agonistas μ (morfina, fentanil, alfentanil).…”
Section: Discussionunclassified